Expression of aryl hydrocarbon receptor in rat brain lesions following traumatic brain injury. Issue 1 (December 2016) - Xu, Kai; Yang, Zicheng; Shi, Rongchen; Luo, Chunxia; Zhang, Zhiren
Abstract Background Aryl Hydrocarbon Receptor (AhR) is a ligand-activated transcription factor with multiple functions operating in a variety of organs, including the brain. Recent studies have revealed that AhR played a functional role in traumatic injuries. This paper aims to study the expression of AhR during the early phase following a traumatic brain injury (TBI) in rat brains by immunohistochemistry. Methods Weight-drop induced TBI was performed in rats. The expression of AhR in brain of TBI rats were examined by immunohistochemistry. Results Neuron expression of AhR in the rat brains of experiment group had been upregulated since day 3 in lesional hemisphere compared to that of the control group and mainly located in the cytoplasm, indicating an inactivated state. Interestingly, the accumulation of AhR+ non-neuron cells became significant as early as 18 h after injury, which had kept increasing until 24 h post injury and then decreased slowly. For AhR+ non-neuron cells, the AhR mainly located in cell nucleus, indicating a reactive status. Furthermore, double staining showed that most AhR+ non-neuron cells co-localized with W3/13, a marker for T lymphocytes, but not with ED-1 (for activated microglia/macrophages) or GFAP (for activated astrocytes), suggesting that most AhR+ non-neuron cells were T lymphocytes. Conclusion This is the first study concerning AhR expression in brains following TBI, and our data demonstrated that AhR was upregulated and activated in T lymphocytes following TBI. More research is needed to make a more conclusive conclusion.